Development of topological method for calculating current distribution coefficients in complex power networks; Results in Physics; Vol. 7 - Akhmetbaev D. S. Dauren Sadykovich; Aubakir D. A. Daurenbek Azenuly; Sarsikeev E. Zh. Ermek Zhaslanovich; Bayniyazov B. A. Bakhtybek Askerovich; Surkov M. A. Michael Aleksandrovich; Rozhkov V. I. Vitaly Igorjevich; Ansabekova G. N. Gulbakyt Nurlybekkyzy; Erbolova A. S. Asel Serikanovna; Suleymenov A. T. Azamat Tynysovich; Tokasheva M. S. Miramgul Serikovna (2017, 2017)
Title screen